Impact of LEDGIN treatment during virus production on residual HIV-1 transcription - Gerlinde Vansant; Lenard S. Vranckx; Irena Zurnic; Dominique Van Looveren; Paulien Van de Velde; Christopher Nobles; Rik Gijsbers; Frauke Christ; Zeger Debyser (Retrovirology, 2019)
Abstract Background Persistence of latent, replication-competent provirus is the main impediment towards the cure of HIV infection. One of the critical questions concerning HIV latency is the role of integration site selection in HIV expression. Inhibition of the interaction between HIV integrase and its chromatin tethering cofactor LEDGF/p75 is known to reduce integration and to retarget residual provirus to regions resistant to reactivation. LEDGINs, small molecule inhibitors of the interaction between HIV integrase and LEDGF/p75, provide an interesting tool to study the underlying mechanisms. During early infection, LEDGINs block the interaction with LEDGF/p75 and allosterically inhibit the catalytic activity of IN (i.e. the early effect). When present during virus production, LEDGINs interfere with proper maturation due to enhanced IN oligomerization in the progeny virions (i.e. the late effect). Results We studied the effect of LEDGINs present during virus production on the transcriptional state of the residual virus. Infection of cells with viruses produced in the presence of LEDGINs resulted in a residual reservoir that was refractory to activation. Integration of residual provirus was less favored near epigenetic markers associated with active transcription. However, integration near H3K36me3 and active genes, both targeted by LEDGF/p75, was not affected. Also in primary cells, LEDGIN treatment induced a reservoir resistant to activation due to a combined early and late effect. Conclusion LEDGINs present a research tool to study the link between integration and transcription, an essential question in retrovirology. LEDGIN treatment during virus production altered integration of residual provirus in a LEDGF/p75-independent manner, resulting in a reservoir that is refractory to activation.